GRI Index 2019 - World Bank (World Bank, Washington, DC, 2019)
The World Bank GRI Index 2019 provides an overview of sustainability considerations within the World Bank`s lending and analytical services as well as its corporate activities. This index of sustainability indicators has been prepared in accordance with the internationally recognized standard for sustainability reporting, the GRI Standards: Core option (https://www.globalreporting.org). The GRI Index covers activities from fiscal year 2019, July 1, 2018, through June 30, 2019.